Memoir Khatijah Sidek : puteri kesatria bangsa - Khatijah Sidek , 1918-1982 (Siri memoir Universiti Kebangsaan Malaysia, 1995)
Autobiography of Khadijah Sidek, 1918-1982, activist in women emancipation in Malaysia